Unformatted text preview: X i are independent Bernoulliâ€™s. 3. Poisson: E e tX = X e tk eÎ» Î» k k ! = eÎ» X ( Î»e t ) k k ! = eÎ» e Î»e t = e Î» ( e t1) . 4. Exponential: E e tX = Z âˆž e tx Î»eÎ»x dx = Î» Î»t if t < Î» and âˆž if t â‰¥ Î» . 5. N (0 , 1): 1 âˆš 2 Ï€ Z e tx ex 2 / 2 dx = e t 2 / 2 1 âˆš 2 Ï€ Z e( xt ) 2 / 2 dx = e t 2 / 2 . 6. N ( Î¼,Ïƒ 2 ): Write X = Î¼ + ÏƒZ . Then E e tX = E e tÎ¼ e tÏƒZ = e tÎ¼ e ( tÏƒ ) 2 / 2 = e tÎ¼ + t 2 Ïƒ 2 / 2 . Proposition 12.1. If X and Y are independent, then m X + Y ( t ) = m X ( t ) m Y ( t ) . Proof. By independence and Proposition 11.1, m X + Y ( t ) = E e tX e tY = E e tX E e tY = m X ( t ) m Y ( t ) . 24...
View
Full
Document
This note was uploaded on 12/29/2011 for the course MATH 317 taught by Professor Wen during the Spring '09 term at SUNY Stony Brook.
 Spring '09
 wen
 Bernoulli, Binomial, Variance

Click to edit the document details